ACQUAINTING INVENTIVE MEDIA: E-INK TO TRIGGER STUDENTS’ CREATIVITY IN WRITING RECOUNT TEXTS - Luky Tiasari (Universitas Stikubank (UNISBANK) Semarang, 2018)
One of the foreign languages used in Indonesian schools is English. Before teaching it to the students, teachers should know the characteristics of the students and how to teach them both in spoken and written forms appropriately. It is provided by students to minimize the breakdown of communication in their daily life. In this paper, I would like to propose inventive media: E-INK (Enjoy writing texts using colourful ink) for writing recount texts to the eighth graders of junior high school consisting of three ways: Idyll, Nest and Key. Plomp’s model of Research and Development (1997) was used to develop this product by conducting a preliminary study, development and expert judgements in the evaluation stage. Three results of this research revealed that a) All of the E-INKs’ tasks and activities were suitable for basic competence and the students’ need. b) The E-INK afforded songs to develop the students’ ideas in creating recount texts. c) The writing template offered save and edit models pertaining to the students’ interest. Keywords: E-INK: Idyll, Nest and Key, Writing: recount texts